2022
DOI: 10.1002/art.42033
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Mitochondrial Transcription Factor A Expression Promotes Mitochondrial Damage to Drive Fibroblast Activation and Fibrosis in Systemic Sclerosis

Abstract: Objective Mitochondrial transcription factor A (TFAM) controls the transcription of core proteins required for mitochondrial homeostasis. This study was undertaken to investigate changes in TFAM expression in systemic sclerosis (SSc), to analyze mitochondrial function, and to evaluate the consequences for fibroblast activation. Methods TFAM expression was analyzed by immunofluorescence and Western blotting. The effects of TFAM knockout were investigated in cultured fibroblasts and in murine models of bleomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…CASQ1 is a coding gene for CASQ1, a primary calcium ion buffer in the sarcoplasmic reticulum of skeletal muscle and a modulator of ryanodine receptor type 1 activity. Deregulation of CASQ1 has been linked to enhanced oxidative stress and mitochondrial damage, 24 mechanisms that have been implicated in the pathogenesis of SSc and might thus drive disease progression 25 . We and others identified STAT3 signaling as an important downstream regulator of fibroblast and leukocyte activation in SSc, and inhibition of STAT3 signaling has been shown to ameliorate experimental fibrosis 26–31 .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…CASQ1 is a coding gene for CASQ1, a primary calcium ion buffer in the sarcoplasmic reticulum of skeletal muscle and a modulator of ryanodine receptor type 1 activity. Deregulation of CASQ1 has been linked to enhanced oxidative stress and mitochondrial damage, 24 mechanisms that have been implicated in the pathogenesis of SSc and might thus drive disease progression 25 . We and others identified STAT3 signaling as an important downstream regulator of fibroblast and leukocyte activation in SSc, and inhibition of STAT3 signaling has been shown to ameliorate experimental fibrosis 26–31 .…”
Section: Resultsmentioning
confidence: 88%
“…Deregulation of CASQ1 has been linked to enhanced oxidative stress and mitochondrial damage, 24 mechanisms that have been implicated in the pathogenesis of SSc and might thus drive disease progression. 25 We and others identified STAT3 signaling as an important downstream regulator of fibroblast and leukocyte activation in SSc, and inhibition of STAT3 signaling has been shown to ameliorate experimental fibrosis. [26][27][28][29][30][31] Consistent with the results obtained by RNASeq on the messenger RNA (mRNA) level, we found AMPK and CASQ1 to be up-regulated in response to S100A4, whereas pSTAT3, the active form of the profibrotic transcription factor STAT3, was down-regulated on S100A4 inhibition (Figure 3).…”
Section: Resultsmentioning
confidence: 90%
“…TFAM is a mitochondrial transcription and replication regulator encoded by a nuclear gene [39,40]. TFAM deficiency leads to a reduction in mitochondrial DNA copy number and severe respiratory chain function defects, accompanied by a significant increase in mitochondrial ROS levels [40][41][42]. Mitochondrial ROS are known to promote necrotic apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial transcription factor A (TFAM) plays an important role in maintaining mitochondrial DNA stability [34]. Studies have shown that a significant decrease in the protein level of TFAM represents a malfunction of mitochondrial function [35], and promoting the increase in TFAM protein level is conducive to alleviating the dysfunction caused by mitochondrial damage. VDAC1 and HSP60 have relatively highly conserved DNA sequences, so they are often used as mitochondrial markers.…”
Section: Discussionmentioning
confidence: 99%